2005
DOI: 10.1007/s10517-006-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Mononuclear Bone Marrow Cells during Reparative Regeneratrion after Acute Myocardial Infarction

Abstract: A randomized controlled study included 44 patients with acute myocardial infarction. It was found that intracoronary injection of bone marrow mononuclear cells is safe, ensures fixation of the injected cells in the myocardium, reduces blood levels of IL-1beta and TNF-alpha, increases the content insulin-like growth factor, and does not provoke malignant arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 1 publication
0
33
0
1
Order By: Relevance
“…Increase in peak VO 2 without influence on duration of exercise was found in another trial [4]. In other studies influence of BMSC on exercise tolerance assessed in METs [8] or in prolongation of distance in 6 min walk test [14] was not confirmed. In trials where positive effect of BMSC was observed, baseline LVEF was similar to ours, but the patients were older [4].…”
Section: Disscussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Increase in peak VO 2 without influence on duration of exercise was found in another trial [4]. In other studies influence of BMSC on exercise tolerance assessed in METs [8] or in prolongation of distance in 6 min walk test [14] was not confirmed. In trials where positive effect of BMSC was observed, baseline LVEF was similar to ours, but the patients were older [4].…”
Section: Disscussionmentioning
confidence: 81%
“…can migrate to other organs, like lungs, liver, spleen and bone marrow [14]. Its influence on these organ function is unknown.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all trials, primary angioplasty, the principal form of MI treatment, was used alone or in combination with bone marrow stem cell administration, via intracoronary infusion 24. Overall, the clinical trials revealed that limited engraftment of the infused cells was a major issue, as only approximately 2–7% of the infused cells were successfully found in the heart 24 h post transplantation 25 26. In order to improve the trial efficacy, other studies were designed where, instead of infusing autologous unfractionated bone marrow mononuclear cells, enriched fractions containing bone marrow-derived stem cells (BMSC), haematopoietic stem cells (HSC), endothelial progenitor cells (EPC) or mesenchymal stem cells (MSC) were used.…”
Section: Non-cardiac Adult Progenitor Cell-based Therapiesmentioning
confidence: 99%
“…Quantitative data from animal as well as human studies indicate that only a small fraction of injected cells is retained within the myocardium (9,23,35,41). Apart from cell washout, a large number of transplanted cells are also lost via cell death in the hostile inflammatory milieu (99,108).…”
Section: Determining the Optimal Bmc Numbermentioning
confidence: 99%